2023
DOI: 10.29333/ijese/13203
|View full text |Cite
|
Sign up to set email alerts
|

Examining some of the challenges students face in learning about rearrangement reactions in organic chemistry

Abstract: Organic chemistry course is considered one of the most difficult courses students have to take as part of their academic science and engineering requirements. The purpose of this research project is to examine students’ perceptions about the challenges they face in learning about rearrangement reactions and their approaches to improve their learning and performance in the concepts while learning organic chemistry. The research investigation took place at the City College of New York, a minority serving, commut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…This finding provides further support for previous claims made by various authors regarding difficult topics in organic chemistry. These topics include the description and representation of organic compounds (Salame & Khalil, 2023), the characteristics of organic compounds (Anderson & Bodner, 2008), and the study of stereochemistry (Durmaz, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding provides further support for previous claims made by various authors regarding difficult topics in organic chemistry. These topics include the description and representation of organic compounds (Salame & Khalil, 2023), the characteristics of organic compounds (Anderson & Bodner, 2008), and the study of stereochemistry (Durmaz, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a noticeable inclination toward research in chemistry education, with a specific focus on organic chemistry due to the identification of student difficulties and misconceptions, and the underlying causes of these challenges (Anim-Eduful & Adu-Gyamfi, 2022b; Ayalew, 2015;Salame & Khalil, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The application of acid–base concepts in organic chemistry requires both memorization and the ability to reason through structural effects on acidity and basicity. Previous research , demonstrated students have a substantial preference to rely on memorization of acid–base examples in both general and organic chemistry. Students preferred to analyze reactions and mechanisms as a simple recombination of atoms versus thinking through the conceptual logic of transformations in hand.…”
Section: Introductionmentioning
confidence: 99%
“…Organic reactions and their mechanisms are considered some of the most challenging topics in organic chemistry courses due to the large number of chemical reactions covered in the discipline. This immense amount of information can discourage students, leading to a significant proportion experiencing ineffective learning and ultimately dropping out at rates ranging from 50% to 60%. …”
Section: Introductionmentioning
confidence: 99%